Oblongifolin B isolated from Brazilian red propolis exhibits anti-methicillin-resistant Staphylococcus aureus action and modulates macrophage activity - Almeida, Jônatas Felipe dos Santos [UNESP]; Honorio, Mariana da Silva [UNESP]; Lopes, Emilly Camargo [UNESP]; Ripari, Nicolas [UNESP]; Fernandes Júnior, Ary [UNESP]; Tanimoto, Matheus Hikaru; Bastos, Jairo Kenupp; Sforcin, José Maurício [UNESP] (Oxford University Press (OUP), 2025)
OBJECTIVES: Methicillin-resistant Staphylococcus aureus (MRSA) is a Gram-positive bacterium found in hospital-acquired infections, particularly in immunosuppressed individuals. Brazilian red propolis is a beekeeping product with antimicrobial and immunomodulatory properties. Its composition includes flavonoids and benzophenones, such as oblongifolin B (OBLB). This study investigated the antibacterial activity of OBLB isolated from Brazilian red propolis against MRSA in vitro and its modulatory effects on macrophages. METHODS: The activity of OBLB was assessed both alone and in combination with antimicrobials. The minimum inhibitory and minimum bactericidal concentrations were determined for the USA300 MRSA strain and for a clinical isolate. The interaction between OBLB and the antimicrobials against MRSA was analysed using the checkerboard method. The effects of OBLB on THP-1 cells differentiated into macrophages were analysed regarding cytokine and eicosanoid production, cell surface marker expression, bactericidal activity, and hydrogen peroxide production. KEY FINDINGS: OBLB exhibited anti-MRSA activity and had no synergistic effects with antimicrobials or cytotoxic effects on macrophages. It stimulated tumor necrosis factor-α and interleukin-1β production, CD80 expression, and increased the bactericidal activity of macrophages suppressed or not by dexamethasone against MRSA. CONCLUSIONS: OBLB exerted anti-MRSA properties and modulated macrophage activity, suggesting it is a potential candidate in new therapeutic approaches for MRSA infections.